ТҮРКОЛОГИЯДА РЕҢ АҢЛАТЫЎШЫ ЛЕКСЕМАЛАРДЫҢ ҮЙРЕНИЛИЎ ТАРИЙХЫ - Оразымбетова, Ш.А. (ILIM hám JÁMIYET, 2024)
The article is dedicated to the review of linguistic studies conducted by Turkologists in the relatively new field of color linguistics. An analysis of the research on color-designating lexemes in various languages of the Common Turkic group has shown that most color terms in Turkic languages, having common roots, are an ancient means of reflecting Turkic mentality. Therefore, basic color terms in Turkic languages have Proto-Turkic origins, and a parallelism in the associative use of “primary” color names is observed across all Turkic languages, which is largely determined by the common origin of the color-designating adjectives.